Thyroid - Kini, Sudha R (Igaku-Shoin, 1996)
Henry Ford Hospital, Detroit, MI. Second edition of a reference for pathologists and cytopathologists on the diagnosis of specific thyroid conditions. Previous edition 1987. Halftone illustrations. 3 U.S. contributors. DNLM: Thyroid Neoplasms - diagnosis.
Guides to clinical aspiration biopsy
Keywords: jehlová biopsie; Biopsy, Needle; Thyroid Neoplasms; histologie; patologie; endokrinologie; nádory štítné žlázy; diagnostika